Boundaries, borders, and limits. A phenomenological reflection on ethics and euthanasia - Leget, C. (Journal of medical ethics, 2006)
The subject of euthanasia divides both people and nations. It will always continue to do so because the arguments for and against this issue are intrinsically related to each other. This paper offers an analysis of the interrelation of the arguments, departing from a phenomenology of boundaries. From the participant perspective the boundary of euthanasia appears as a limit. From a helicopter perspective it appears as a border. Reflecting on both perspectives they turn out to complement each other: the positive effects of the former correspond to the negative effects of the latter. In order to see how this interrelation of viewpoints works out in the case of euthanasia a paradigmatic case is analysed from the perspective of the patient, the doctor, and the family. This phenomenological analysis does not directly lead to normative conclusions. It helps by both paying attention to, and dealing with, the complexity of the issue with intellectual honesty.